2007
DOI: 10.1007/s00259-006-0338-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical radionuclide therapy dosimetry: the quest for the “Holy Gray”

Abstract: IntroductionRadionuclide therapy has distinct similarities to, but also profound differences from external radiotherapy.ReviewThis review discusses techniques and results of previously developed dosimetry methods in thyroid carcinoma, neuro-endocrine tumours, solid tumours and lymphoma. In each case, emphasis is placed on the level of evidence and practical applicability. Although dosimetry has been of enormous value in the preclinical phase of radiopharmaceutical development, its clinical use to optimise admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(67 citation statements)
references
References 72 publications
0
64
0
3
Order By: Relevance
“…Salivary parenchymal functions and symptoms after 131 I therapy were not studied. Although it is accepted that radiation-absorbed dose to normal tissue in radionuclide therapy is able to predict toxicity (17)(18)(19), investigations of the dose-effect relation for the salivary glands in 131 I therapy remain essential. Second, we investigated the effect of only the timing of salivary gland stimulation, and if the sour prescription in the study had been less stringent, the study would have been insufficiently powerful to detect the effect of sour stimulation on salivary absorbed dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary parenchymal functions and symptoms after 131 I therapy were not studied. Although it is accepted that radiation-absorbed dose to normal tissue in radionuclide therapy is able to predict toxicity (17)(18)(19), investigations of the dose-effect relation for the salivary glands in 131 I therapy remain essential. Second, we investigated the effect of only the timing of salivary gland stimulation, and if the sour prescription in the study had been less stringent, the study would have been insufficiently powerful to detect the effect of sour stimulation on salivary absorbed dose.…”
Section: Discussionmentioning
confidence: 99%
“…As is well recognized, normal-tissue radiation-absorbed dose delivered by an administered radiopharmaceutical correlates with attendant tissue toxicity (17)(18)(19). Dosimetry is thus important both for determining the limit beyond which administered radiation would cause harmful side effects and for enabling assessment of the effects of various protective measures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the absorbed doses in the target and critical tissues is also needed to optimize the activity to inject (5)(6)(7)(8)(9). Until recently, investigators focused on the major emission of 90 Y (i.e., b-rays) that was imaged with SPECT using the bremsstrahlung x-rays, the energy spectrum of which is continuous.…”
mentioning
confidence: 99%
“…A recent review by the EANM Dosimetry Committee identified 48 papers (out of 79 surveyed) employing the use of radionuclide dosimetry showing a strong correlation between absorbed dose and the tumour response & toxicity over a wide range of radionuclide treatments (including 90 Y-RE) [9], and many works have noted the lack of randomized trials comparing dosimetry-based radionuclide therapy to fixed dosing, or dosing per kg body weight [10,11]. For routine use, there is a requirement of standardized procedures for absorbed dose calculations [12] and improved reliability of radiobiological models used to convert dosimetric data to biologic endpoints [13].…”
Section: Introductionmentioning
confidence: 99%